The Evaluation of Land Suitability for Arabica Coffee Cultivation (Coffea arabica L.) in Nagari Koto Gadang Guguk, Solok Regency, West Sumatra - Maidia Solfianti; Gunadi Gunadi (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian Universitas Andalas, 2026)
Arabica coffee (Coffea arabica L.) is one of the high economic value plantation commodities, where the level of production is largely determined by land suitability. Scientific information related to specific land suitability in potential areas, such as Solok Regency, is still minimal. This research was conducted in Nagari Koto Gadang Guguk, Gunung Talang District, West Sumatra, with the aim of assessing the level of land suitability for Arabica coffee cultivation. The research was conducted from August to November 2024 through field surveys, laboratory analysis, and Geographic Information System (GIS)-based mapping at a scale of 1:50,000. Analysis included soil physical characteristics (texture, effective depth, drainage), chemical properties (pH, organic carbon, cation exchange capacity, base saturation), as well as topography and climate factors. Results showed that the study land was dominated by dusty loam to dusty clay textures with medium to high C-organic content (2.68-3.12%), slightly acidic pH (5.50-6.18), medium-high CEC values (21.53-32.54 cmol kg-¹), and base saturation of 42.53-68.23%. From the evaluation results, four land units (SL1-SL4) were categorized as S3 class (marginally suitable) with the main constraints of excess rainfall (2,817-3,000 mm/year) and slope (9-40%). Meanwhile, SL5 is categorized as class N (unsuitable) due to drainage problems. The potential to increase land suitability is still open through the application of soil and water conservation, terrace construction, use of adaptive varieties, and improvement of soil and water management. The overall results confirm the importance of land suitability evaluation as a foundation for sustainable Arabica coffee management in the tropical highland region. Key words : Arabica coffee, land suitability, soil conservation, GIS